2020
DOI: 10.3390/diagnostics10040187
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Point-of-Care Tests for the Determination of Antibodies after Acellular Pertussis Vaccination

Abstract: Most of the current serological diagnosis of pertussis is based on pertussis toxin (PT) IgG antibodies and does not differentiate between vaccination and infection-induced antibodies. PT is included in all of acellular pertussis vaccines available in the world. Multiplex testing of non-vaccine antigen-related antibodies has the potential to improve the diagnostic outcome of these assays. In this study, we developed a quantitatively spatial multiplex lateral flow immunoassay (LFIA) for the detection of IgG anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This study demonstrated that the multiplex measurement of PT and ACT antibodies can improve the serological diagnosis of pertussis. In combination with a rapid and easy-to-perform multiplex platform with lateral flow assays [ 12 , 20 ], serological testing could be performed very flexibly and even within a short period from pertussis vaccination. The test would be of particular use for serological diagnosis concerning children and adolescents who have recently received a booster vaccine, and in cases when the vaccination background of a patient is uncertain with regard to personal recalling or knowledge, or due to a lack of extensive records of the timing of the latest vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrated that the multiplex measurement of PT and ACT antibodies can improve the serological diagnosis of pertussis. In combination with a rapid and easy-to-perform multiplex platform with lateral flow assays [ 12 , 20 ], serological testing could be performed very flexibly and even within a short period from pertussis vaccination. The test would be of particular use for serological diagnosis concerning children and adolescents who have recently received a booster vaccine, and in cases when the vaccination background of a patient is uncertain with regard to personal recalling or knowledge, or due to a lack of extensive records of the timing of the latest vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of the strips and the test procedure were done similar to Knuutila et al with the following modifications [ 12 ]: 1000 ng/cm of ACT was used as the second test line, between native PT (GlaxoSmithKline Biologicals, S.A., Rixensart, Belgium) and the control line ( Figure 1 and Figure S1 ). 06/142 sera, in-house PT-positive and PT-negative controls were included for each run.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another natural source of deviation between the assays was derived from the choice of a label in the LF assay, as the protein A conjugate also binds to IgA and IgM antibodies [27]. This will potentially reduce the correlation between the two assays because the oral fluid ELISA is designed to measure only IgG.…”
Section: Resultsmentioning
confidence: 99%
“…All samples were tested at least in duplicate. After absorbing the sample, 6×10 7 protein A (#RL240425; Thermo Fisher Scientific) label, conjugated with activated fluoro-Max carboxyl modified microparticles, containing Eu-nanoparticles (diameter 99 nm; Thermo Fisher Scientific) [27] were applied to the LF strips in dipstick-format with 60 µl of HEPES buffer. Protein A binds to various mammalian Fc portions of immunoglobulins, including anti-human IgA, IgG and IgM.…”
Section: Lateral Flow Immunoassaysmentioning
confidence: 99%